(3GdfXGe GdbGfhfj dYbhO GdJTjjO hGdJTZjd hfbd GdedcjI (B/ s - (3NGdO Hf eMeO YHOGddg GdYWjIs; (3eMeO eMeO HOQGf (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1999)
(3JTJed gPg GdQSGdI Ydi GdHGH GdChd GdPj jJfGhd eGgjI YbhO GdHfGA hGdJTZjd hfbd GdedcjI, hGdHGH GdKGfj jJfGhd GdeQGMd GdeNJdaI GdJj JeQ HgG eTQhYGJ GdHhJ, hGdHGH GdKGdK GdPj jJfGhd GdJRGeGJ hMbhb CWQGa YbhO GdHhJ hJShjI GdefGRYGJ(B.s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B1999.s
Keywords: (3YbhO GdHfGAs; (3YbhO GdJTZjds; (3YbhO fbd GdedcjIs; (3YbhO GdHhJs; (3GdGeJjGRs; B.O.T; (3fbd GdJcfhdhLjGs; (3GdJMcjes; (3YbhO GdHfGAs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 1999